A Case Study of Islamic Financial Institutions of Pakistan: Challenges & Growth - Nadiya Shahzad (Universitas Muhammadiyah Yogyakarta, 2021)
The purpose of this research paper was to find the growth of Islamic financial institutions for the economic development of Pakistan. Also, this study highlighted issues and constraints against the growth of Islamic banking in Pakistan. Islamic banking was based on the current model of products of conventional banking to achieve the general objectives of Islamic economic that was insufficient and based on the fair distribution of economic profits and render the Islamic financing more efficient from their conventional equivalents. The study contained major issues such as lack of treasury and liquidity risk management, regulatory, legal and tax environment, several interpretations of Sharia ruling, lender of last resort facility, lack of Sukuk offered in secondary markets. The study found that in Pakistan, the growth and development of Islamic financial institutions were very low compared to other Muslims and non-Muslim countries need to improve the performance of the Islamic banks' mode, and it is not too late to plan on those constraint strategies and implantation to avoid those constraints. This study will facilitate privileged management to lay down policies so that the Islamic banking operations develop low-income countries such as Pakistan.